(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
The study aimed to identify the concept of the Fifth Industrial Revolution and the role of its dimensions in influencing the performance of the Jordanian Islamic banks, in conjunction with the technological advancements and the global trend towards digitization. Additionally, the study shed light on the changes that the Fifth Industrial Revolution in the banking sector brings about on work processes and banking operations, and contributed to enriching the theoretical literature on the role of the Fifth Industrial Revolution and each of its dimensions in the performance of Jordanian Islamic banks. The study employed a quantitative analytical approach. The results of the study showed that the Fifth Industrial Revolution has a significant positive impact on the performance of Jordanian Islamic banks. Modern technology has contributed to improving operational efficiency by reducing costs, accelerating transactions, and minimizing human errors. It has also led to the development of financial products and services, with the creation of Sharia-compliant digital solutions, which have enhanced financial inclusion and customer satisfaction. In conclusion, the study recommends that Islamic banks adopt the technologies of the Fifth Industrial Revolution to improve their performance and ensure their sustainability in a developing, while maintaining the balance between innovation and compliance with Sharia controls.